2015
DOI: 10.1007/s11743-015-1743-1
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Systems Based on Erucyl Amidopropyl Betaine and Nanoparticles: Self‐Organization and Rheology

Abstract: The aggregation behavior and flow characteristics of systems based on zwitterionic surfactant, erucyl amidopropyl betaine, silica and alumina nanoparticles in a wide range of surfactant concentrations from molecular to micellar solutions were studied using surface tensiometry, conductometry, dynamic and electrophoretic light scattering, and rheology techniques. The adsorption of zwitterionic surfactant molecules occurs on both positively and negatively charged surfaces via an electrostatic interaction mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…When the nanoparticles have opposite charges with the headgroup of surfactants, the electrostatic interaction prevails, and the surfactants are electrostatically attracted to the surface of nanoparticles through charged head groups. 245,289,301,302 In this case, surfactant bilayers wrapping nanoparticles are formed (Figure 11(a)). When the nanoparticles are uncharged hydrophobic particles, the hydrophobic interaction is dominant, and the surfactants are chemically adsorbed on the particle surfaces through hydrophobic tails to form surfactant monolayers (Figure 11(c)).…”
Section: Counterion Salt Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…When the nanoparticles have opposite charges with the headgroup of surfactants, the electrostatic interaction prevails, and the surfactants are electrostatically attracted to the surface of nanoparticles through charged head groups. 245,289,301,302 In this case, surfactant bilayers wrapping nanoparticles are formed (Figure 11(a)). When the nanoparticles are uncharged hydrophobic particles, the hydrophobic interaction is dominant, and the surfactants are chemically adsorbed on the particle surfaces through hydrophobic tails to form surfactant monolayers (Figure 11(c)).…”
Section: Counterion Salt Effectmentioning
confidence: 99%
“…Several hypotheses about the interaction mechanism between nanoparticles and WLMs have been put forward in the literature. It is usually divided into two stages: surfactant adsorption and micelles fusion. When the nanoparticles have opposite charges with the headgroup of surfactants, the electrostatic interaction prevails, and the surfactants are electrostatically attracted to the surface of nanoparticles through charged head groups. ,,, In this case, surfactant bilayers wrapping nanoparticles are formed (Figure (a)). When the nanoparticles are uncharged hydrophobic particles, the hydrophobic interaction is dominant, and the surfactants are chemically adsorbed on the particle surfaces through hydrophobic tails to form surfactant monolayers (Figure (c)). , Meanwhile, when the surface charge of nanoparticles is the same as that of surfactants, surfactants can still adsorb on the surface through hydrophobic interaction to form semimicelles (Figure (b)). , In the next stage, the nanoparticles coated by surfactants interact with WLMs formed by surfactant self-assembly (Figure (d) and (e)).…”
Section: High-temperature-resistant Ves Fracturing Fluidsmentioning
confidence: 99%
“…At the same time, zwitterionic surfactants, which are low-toxic, biodegradable, and safe even for the sensitive child skin, are more promising in environmental terms [24]. However, just one work devoted to the effect of nanoparticles on the rheological properties of the solutions of zwitterionic surfactants has been published so far [25]. It was shown that the addition of negatively charged silica nanoparticles (0.3-0.8 wt %) with a radius of 12 nm to a solution of the wormlike micelles of erucyl amidopropyl dimethyl betaine with a long C22 tail increases the viscosity of the system twofold.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to study the effect of nanoparticles on the rheological properties and structure of wormlike micelles based on a biodegradable zwitterionic surfactant with a long C18 tail, oleyl amidopropyl dimethyl carboxybetaine (OAB), obtained from biorenewable resources, vegetable oils, with a small addition of an anionic surfactant, sodium dodecyl sulfate (SDS). As opposed to the overwhelming majority of previous works on nanocomposite systems based on wormlike surfactant micelles [17][18][19][20][21][22][23]25], platelike nanoparticles with a high specific surface compared with commonly used spherical particles were used as a filler. This provided a larger surface for interaction with micellar chains.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the pure micellar solution, the system with a moderate concentration of nanoparticles has a larger zero‐shear viscosity. Gaynanova et al investigated the aggregation behavior of a compound system constructed by wormlike micelles and silica nanoparticles (Gaynanova et al, ). They found that electrostatic interaction caused the adsorption of zwitterionic surfactants on the surface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%